RESPON CABAI MERAH (Capsicum annuum L.) TERHADAP PERBEDAAN DOSIS KOMPOS ALANG-ALANG DAN PUPUK NPK - Lusiana Siregar; Mapegau .; Made Deviani Duaja (Bioplantae, 2014)
This research was conducted at Teaching and Research Farm of Agriculture Faculty, University of Jambi, Mendalo Darat, Muaro Jambi. The aim to determine whether compost of Bladygrass can increase the growth and yield of red chili. The design used in this experiment is a randomized complete block design (RCBD) with combination dose of NPK and compost of Bradygrass as a factor :10 ton ha-1 compost + NPK 0 kg ha-1, 10 ton ha-1 compost  + NPK 200 kg ha-1, 10 ton ha-1 compost+NPK 400 kg ha-1, 20 ton ha-1 compost + NPK 0 kg ha-1, 20 ton ha-1 compost + NPK 200 kg ha-1 and 20 ton ha-1 compost + NPK 400 kg ha-1. The experiment consisted of four replications. The variables measured were plant height, number of fruits per plant, fruits weight per plant and yield. The results showed dose, 10 ton ha-1 of bradygrass compost  + NPK 200 kg ha-1 gave the highest number of fruits per plant,  weight of fruit per plant and   the highest yield of red chili but  non significant difference for plant height. Keywords: Red chilli, compost, bradygrass, pepper